2020
DOI: 10.1016/j.jinf.2020.05.053
|View full text |Cite
|
Sign up to set email alerts
|

Cancer in intensive care unit patients with COVID-19

Abstract: In a recent article, Ma et al. suggested that patients with cancer will be more susceptible to severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) infection and complications, although data on COVID-19 and malignancies remain limited. 1 In a small study, Liang et al. noted that patients with cancer were more likely to experience severe sequelae of SARS-CoV-2 infection, such as intensive care admission, invasive ventilation or death. 2 However, Wang and Zhang argued that the most important morbidity f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
(3 reference statements)
0
5
0
1
Order By: Relevance
“…Whilst these studies indicate that the prevalence of cancer in patients with COVID‐19 may be higher than in the general population, not all studies have found this to be the case. For example, in 1 307 patients who were admitted to intensive‐care units (ICUs) in Russia, only 2·4% had a history of cancer (none of which were haematological) and the authors concluded this was a similar prevalence to that in the general population 10 . Zhou et al 11 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst these studies indicate that the prevalence of cancer in patients with COVID‐19 may be higher than in the general population, not all studies have found this to be the case. For example, in 1 307 patients who were admitted to intensive‐care units (ICUs) in Russia, only 2·4% had a history of cancer (none of which were haematological) and the authors concluded this was a similar prevalence to that in the general population 10 . Zhou et al 11 .…”
Section: Resultsmentioning
confidence: 99%
“…For example, in 1 307 patients who were admitted to intensive-care units (ICUs) in Russia, only 2Á4% had a history of cancer (none of which were haematological) and the authors concluded this was a similar prevalence to that in the general population. 10 Zhou et al 11 showed that in 191 patients who were admitted into one of two hospitals in the Wuhan province only two had a history of carcinoma. Other cohorts (n = 41-201) of patients with COVID-19 have also been published with only one patient with malignancy in each of the cohorts.…”
Section: Is Cancer a Risk Factor For Developing Covid-19?mentioning
confidence: 99%
“…[12] Likewise, another study conducted in Wuhan, China disclosed that among cancer patients, lung cancer was 25% [13]. Further related studies in Russia stated that as was expected, lung and breast cancers were the most common type malignancies within cancer patients (2.4%) [14]. In addition, another finding from a similar study indicates that in England, patients with a uterine cancer had an incidence and prevalence rate of 8.6% & 6.3% and for bone cancer were 28.3% and 5.7% respectively [15].…”
Section: Resultsmentioning
confidence: 82%
“…Data analyses was performed by Microsoft Excel and Stata version 15 software (StataCorp, Texas, USA)(Stata including population characteristics (including total number of study subjects, age, sex and outcome i.e. mortality associated with SARS CoV-2 infection).The included studies were from China (n = 9) (Dai et al, 2020;He et al, 2020;Meng et al, 2020;Zhang H et al, 2020;Tian et al,2020), the United States (n = 5) (Kalinsky et al, 2020;Luo et al, 2020;Mehta et al, 2020;Robilotti et al, 2020;, Italy (n = 4) (Bogani et al, 2020;Fattizzo et al, 2020;Gallo et al, 2020;Stroppa et al, 2020), Spain (n = 2) (Rogado et al, 2020;Yarza et al, 2020), the United Kingdom (n =5) (Aries et al, 2020;Russell et al 2020;Shah et al, 2020;Shi et al, 2020;Lee et al, 2020), France (n = 2) (Basse et al, 2020;Vuagnat et al, 2020), Brazil (n=1) ( de Melo et al, 2020), Belgium (n = 1) ( Lattenist et al, 2020) , Russia (n=1) ( Moiseev et al, 2020) and one study from Europe included patients from 8 countries (Garassino et al, 2020). Recruitment in these 18 studies was from December 17 th 2019 to June17 th 2020.…”
Section: Discussionmentioning
confidence: 99%